1998
DOI: 10.1034/j.1600-0412.1998.770503.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental expression of endothelial constitutive nitric oxide synthase mRNA in pregnancy complicated by preeclampsia

Abstract: Our findings indicate that the increased placental expression of ecNOS mRNA might reflect a compensatory mechanism in the disturbed uterine circulation seen in PE and/or SGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…However, they observed a lower activity of endothelial nitric oxide synthase where the uterine and placental vessels meet and increased uterine artery resistance in preeclamptic women compared to healthy pregnant women. Nasiell et al and Schiessl et al found significantly increased placental expression of endothelial nitric oxide synthase in pregnancies complicated by preeclampsia [37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…However, they observed a lower activity of endothelial nitric oxide synthase where the uterine and placental vessels meet and increased uterine artery resistance in preeclamptic women compared to healthy pregnant women. Nasiell et al and Schiessl et al found significantly increased placental expression of endothelial nitric oxide synthase in pregnancies complicated by preeclampsia [37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that eNOS plays a significant, pathological role in the manifestation of preeclampsia (PE), the proteinuric and/or edematous form of HP [Seligman et al, 1994; Lyall et al, 1995; Nasiell et al, 1998; Norris et al, 1999]. Although circulating levels of nitrite and the oxidative production of NO are decreased in patients with PE [Seligman et al, 1994], total nitrate levels are increased in the fetoplacental, uteroplacental, and peripheral circulation [Lyall et al, 1995; Norris et al, 1999] as a result of the increased placental expression of eNOS mRNA in PE [Nasiell et al, 1998]. These increases might be part of a compensatory mechanism in the disturbed uterine circulation seen in PE [Nasiell et al, 1998; Norris et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Although circulating levels of nitrite and the oxidative production of NO are decreased in patients with PE [Seligman et al, 1994], total nitrate levels are increased in the fetoplacental, uteroplacental, and peripheral circulation [Lyall et al, 1995; Norris et al, 1999] as a result of the increased placental expression of eNOS mRNA in PE [Nasiell et al, 1998]. These increases might be part of a compensatory mechanism in the disturbed uterine circulation seen in PE [Nasiell et al, 1998; Norris et al, 1999]. Recently, a missense variant in exon 7 of the eNOS gene ( NOS3 ) that encodes an aspartic acid (Asp298) instead of a glutamine (Glu298) at residue 298 was identified [Yoshimura et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that NOS3 plays a significant pathological role in the manifestation of PE. [14][15][16][17] A variant of the NOS3 in which glutamine (Glu298) is substituted for aspartic acid (Asp298) at residue 298 was reported to be significantly associated with HP, including PE, 5 after significant associations of this variant with coronary spasm 18 and myocardial infarction 19,20 had been reported.…”
Section: Patientsmentioning
confidence: 99%